SeaLOWT - Impact of Sea Ice Loads on Global Dynamics of Offshore Wind Turbines : Schlussbericht ... - Popko, Wojciech; Aghaei, Ali; Schümann, Björn; Smolka, Ursula; Tautz-Weinert, Jannis; Wihlfahrt, Urs; Kellner, Leon; Ehlers, Sören (Fraunhofer IWES, 2021)
Illustrationen, Diagramme ...